Girl Power, transgression and the embodiment of the image: The rise of Enjo-kōsai and hyper-sexual economy in post-bubble Japan. Issue 1 (1st April 2017) - Reisel, Mary
Enjo-kōsai, the term attributed to the practice of teenage girls selling dates and sex to older men, became a major controversial issue in Japan in the nineties, followed by political debates and public concerns regarding the nature of the habit and its social and ethical consequences. The article investigates the origin of enjo-kōsai and its development from a trivial subculture game to an actual practice defining sexual conduct and creating rising moral panic all over the country. Drawing on a long ethnographic research including 96 individual interviews and thousands of online surveys, the research explores the ambiguous forms of manipulation and control exercised by the hegemony of the media and fashion magazines in order to promote enjo-kōsai and rebalance the power relations between the teenager girls and their buyers. Based on participants' testimonies, the study tracks the historical events while following the rise of Girl Power ideologies of empowerment and liberation versus the opposing political pressure that attempted to restore and reinforce traditional images of submissive femininity. It also attempts to contextualize the enjo-kōsai boom within the social changes and economic turbulences that Japan had gone through during the post-bubble decade.